INNOVATIVE APPROACH TO FINANCING EXPORTING COMPANIES (Modern education and development, 2024)
The national economy development to a qualitatively new level, as well as introduction of innovations requires a radical reconsideration of the role of exporting companies which hold a particular position  have a place in the economic development. This thesis describes the financing processes of exporting enterprises.